Production and properties of health-promoting proteins and peptides from bovine colostrum and milk - Korhonen, H. J. (Cellular and Molecular Biology, 2013)
The high nutritive value and diverse functional properties of milk proteins are well known. Beyond these qualities, milk proteins have attracted growing scientific and commercial interest as a source of biologically active molecules. Such proteins are found in abundance in colostrum which is the initial milk secreted by mammalian species during late pregnancy and the first few days after birth of the offspring. The best characterized colostrum-based bioactive proteins include alpha-lactalbumin, beta-lactoglobulin, immunoglobulins, lactoferrin, lactoperoxidase and growth factors. All of them can nowadays be enriched and purified on an industrial scale from bovine colostral whey or cheese whey. These native proteins exhibit a wide range of biological activities that are known to affect the digestive function, metabolic responses to absorbed nutrients, growth and development of organs and disease resistance. Also, some of these proteins may prove beneficial in reduction of the risks of chronic human diseases reflected by the metabolic syndrome. It is speculated that such potentially beneficial effects are partially attributed to bioactive peptides derived from intact proteins. These peptides can be liberated during gastrointestinal digestion or fermentation of milk by starter cultures. The efficacy of a few peptides has been established in animal and human studies and the number of commercial products supplemented with specific milk peptides is envisaged to increase on global markets. Bovine colostrum appears as a highly potential source of biologically active native proteins and peptide fractions for inclusion as health-promoting ingredients in various food applications.